PENGELOLAAN KONTEN INSTAGRAM SEBAGAI MEDIA PEMASARAN OBJEK WISATA ALAM - Arkam, Nur; Tenri Sessu, We Patappari (ADMIT: Jurnal Administrasi Terapan, 2023)
This study aims to create marketing content in the form of short video content, image content that uses the Instagram feature as a medium to market natural tourism objects on the Disparpora account of Soppeng Regency. The research method used in this research is descriptive qualitative. This qualitative descriptive approach uses data retrieval and data collection through document review and semi-structured interviews by asking questions to several related parties who can assist researchers in the research process. The results of this study indicate that by using content marketing elements, namely Design, Current Event, The Reading Experience, Time, and Tone, the contents of the posts become more interesting. Output of this research is marketing content in the form of short video content and image content using Instagram features that are used as a medium to market Soppeng Regency's natural tourism objects which are posted on the DISPARPORA account of Soppeng Regency.